FaST-LMM-Select for addressing confounding from spatial structure and rare variants - Listgarten, Jennifer; Lippert, Christoph; Heckerman, David (Nature Genetics, 2013)
A recent report by Mathieson and McVean showed that confounding in genome-wide association studies (GWAS) resulting from spatially structured populations in conjunction with rare variants could not be corrected by currently available statistical genetics methods.
Second International Enterprise Distributed Object Computing Workshop (EDOC )